1983
DOI: 10.1093/jac/12.suppl_c.35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibiotics on polymorphonuclear leukocyte chemiluminescence and chemotaxis

Abstract: Polymorphonuclear leukocyte chemiluminescence and chemotaxis assays were performed on cells obtained from normal individuals and patients with defined defects in chemotaxis or chemiluminescence. After in-vitro pre-incubation with trimethoprim/sulphamethoxazole, its separate components, clindamycin and cefotaxime, normal cells showed some enhancement in chemotaxis and significant increase in chemiluminescence. There was an even more marked increase in chemotaxis when these antibiotics were incubated with cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The indication is that higher concentrations have a lowering effect on the CL response, even though the reduction is not found to be significant by the (less sensitive) Dunnett's test. Although mean peak plasma levels for Bay-n-7133 in mice are between 14 and 16 ,ug/ml (19), the peak plasma level in humans is reported to be only 2.76 pLg/ml (25), a value below the concentration determined to cause a significant reduction in CL activity in our assay. In all other instances, data analyzed by both the trend test and Dunnett's test agreed.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…The indication is that higher concentrations have a lowering effect on the CL response, even though the reduction is not found to be significant by the (less sensitive) Dunnett's test. Although mean peak plasma levels for Bay-n-7133 in mice are between 14 and 16 ,ug/ml (19), the peak plasma level in humans is reported to be only 2.76 pLg/ml (25), a value below the concentration determined to cause a significant reduction in CL activity in our assay. In all other instances, data analyzed by both the trend test and Dunnett's test agreed.…”
Section: Resultsmentioning
confidence: 60%
“…Our data show inhibition of the CL response of mouse spleen cells with ketoconazole at concentrations of 3.0 to 20 jig/ml. Similar conflicting data have been reported for certain antibacterial agents evaluated for their effects on immune cells, including the CL response (15,16,20,21,26). The conflicting reports on the effects of antimicrobial agents on CL may be the result of different methodologies, stimulating agents, and the use of different cell species and types.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In most studies, TMP, alone or in combination, had an inhibitory effect on PMN functions. In a single study, PMN chemotaxis and chemiluminescence were increased, and this effect was also observed with PMNs with defective functions (286). Recently, brodimoprim, in which the methoxy group in position 4 of the benzyl ring of the TMP molecule is replaced by a bromine atom, was shown to display greater lipophilicity and cellular uptake than TMP and had no inhibitory effect on PMN function, whereas TMP impaired the chemiluminescence of these cells (39).…”
Section: Benzylpyrimidines (Trimethoprim and Analogs)mentioning
confidence: 97%